Revision notes in psychiatry - Puri, Basant K.; Hall, Anne D. 1962-; Ho, Roger (CRC Press/Taylor & Francis Group, 2014)
"Revision Notes in Psychiatry, Third Edition continues to provide a clear, comprehensive, and contemporary summary of clinical psychiatry and the scientific fundamentals of the discipline for all candidates taking the MRCPsych and higher psychiatry examinations. Closely following the MRCPsych syllabus, the book is totally updated and revised in a color format and includes links to podcasts and clinical videos.New for the third edition:Comprehensive and follows the format of the MRCPsych examination Contains only key facts and opinions with mnemonics, hints, and tips for examination successLinks to clinical skills videos and podcasts, and refers the candidate to other online resourcesNew colour format with easy-to-remember illustrationsTotally revised to meet the needs of today's candidates, Revision Notes in Psychiatry, Third Edition continues to provide a source of trusted expert information, together with a wealth of new online videos and materials, to ensure examination success for all those taking the MRCPsych and higher examinations in psychiatry."